KORELASI KETERAMPILAN MEMBACA PEMAHAMAN KARANGAN EKSPOSISI DENGAN KETERAMPILAN MENULIS KARANGAN EKSPOSISI - Sari, Fauza Puspita; Basri, Irfani; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is (1) to know the level of reading comprehension skill of students exposition of class XI SMA Negeri 4 Pariaman, (2) to know the level of writing skill of exposition student of class XI SMA Negeri 4 Pariaman, (3) to know correlation of reading comprehension skill written exposition with the writing skills of exposition students of class XI SMA Negeri 4 Pariaman. This research type is quantitative research with correlation method. The results of this study are three, namely (1) reading comprehension skill of exposition is in BS qualification with M 87,07, (2) writing skill of exposition is in qualification B with M 84,66, and (3) there is significant correlation between the reading comprehension skills of the exposition essay with the writing skill of the exposition of the students of class XI SMA Negeri 4 Pariaman. Based on data analysis and discussion, in improving writing skill of exposition is required to read comprehension skill of exposition.Â Kata kunci: Korelasi, membaca pemahaman, karangan eksposisi, keterampilan menulis